INNOVATION IN QURANIC LEARNING AT ELEMENTARY SCHOOL LEVEL (SD) THROUGH THE USE OF ARTIFICIAL INTELLIGENCE (AI) -BASED TECHNOLOGY - Nanda Zaini Badri; Iqbal Amar Muzaki; muhammad makbul (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study discusses the innovation of Qur'anic learning at the elementary school level through the use of Artificial Intelligence (AI)-based technology. The background of this research lies in the low level of students' Qur'anic literacy, which is mainly caused by the limitations of conventional teaching methods and the lack of learning media variations. The research method applied is library research by analyzing various literature related to the implementation of AI in education. The findings show that AI has the potential to enhance the effectiveness, interactivity, and personalization of Qur'anic learning. Examples include speech recognition technology to improve recitation, tahfidz applications to monitor memorization progress, and gamification features to increase students' learning motivation. However, challenges such as limited infrastructure, teachers' readiness to master technology, and curriculum adaptation remain significant issues. In conclusion, the application of AI in Qur'anic learning is a strategic solution to improve students' Qur'anic literacy while supporting the formation of a Qur'anic generation that is religious, adaptive, and technologically literate.